Cigarette Smoke Extract, but Not Electronic Cigarette Aerosol Extract, Inhibits Monoamine Oxidase in vitro and Produces Greater Acute Aversive/Anhedonic Effects Than Nicotine Alone on Intracranial Self-Stimulation in Rats - Harris, Andrew C.; Muelken, Peter; Alcheva, Aleksandra; Stepanov, Irina; LeSage, Mark G. (Frontiers in Neuroscience, 2022)
Conventional tobacco cigarettes appear to have greater abuse liability than non-combusted products such as electronic cigarettes (ECs) and nicotine replacement therapy (NRT). This may be due to the higher levels of behaviorally active non-nicotine constituents (e.g., monoamine oxidase (MAO) inhibitors such as β-carbolines) in cigarette smoke (CS) compared to non-combusted products. To evaluate this hypothesis, the current studies compared the relative abuse liability of CS and EC aerosol extracts containing nicotine and a range of non-nicotine constituents to that of nicotine alone (NRT analog) using intracranial self-stimulation (ICSS) in rats. Effects of formulations on brain MAO activity in vitro and ex vivo were also studied to evaluate the potential role of MAO inhibition in the ICSS study. CS extract contained higher levels of several behaviorally active non-nicotine constituents (e.g., the β-carbolines norharmane and harmane) than EC extract. Nicotine alone reduced ICSS thresholds at a moderate nicotine dose, suggesting a reinforcement-enhancing effect that may promote abuse liability, and elevated ICSS thresholds at a high nicotine dose, suggesting an aversive / anhedonic effect that may limit abuse liability. CS extract elevated ICSS thresholds to a greater degree than nicotine alone at high nicotine doses. Effects of EC extract on ICSS did not differ from those of nicotine alone. Finally, CS extract significantly inhibited MAO-A and MAO-B activity in vitro, whereas EC extract and nicotine alone did not. None of the formulations inhibited MAO measured ex vivo. These findings indicate greater acute aversive / anhedonic effects for CS extract compared to nicotine alone, suggesting lower abuse liability. Although confirmation of our findings using other dosing regimens, preclinical addiction models, and tobacco product extracts is needed, these findings suggest that the centrally-mediated effects of MAO inhibitors and other non-nicotine constituents may not account for the greater abuse liability of cigarettes compared to non-combusted products. Nonetheless, identifying the specific constituent(s) mediating the effects of CS extracts in this study could help clarify mechanisms mediating tobacco addiction and inform FDA product standards.